2021
DOI: 10.36233/0507-4088-2020-65-6-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of herpesviruses in development of diseases of the urogenital tract and infertility in women

Abstract: This review presents the data on the spreading of all known human herpesviruses (НHVs) in female urogenital tract. According to the WHO almost 500 million people worldwide suffer from genital infection caused by НHVs. НHVs were detected in various inflammatory diseases of female upper and lower genital tract (vaginitis and cervicitis), in extrauterine pregnancy (in fallopian tubes), in infertility (cervical channel, endometrium and ovaries). Herpes simplex virus 1 (HSV‑1) was identified for the first time in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Therefore, preventive HSV treatment is urgently needed. Palliser et al 20 suggested that CRISPR/Cas9 combined with vaginal administration against HSV virus envelope glycoprotein B and virus DNA binding protein could protect mice from HSV infection. Mice treated with CRISPR/Cas9 successfully silenced gene expression for 9 days and 2 h before and 4 h after HSV‐2 vaginal challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, preventive HSV treatment is urgently needed. Palliser et al 20 suggested that CRISPR/Cas9 combined with vaginal administration against HSV virus envelope glycoprotein B and virus DNA binding protein could protect mice from HSV infection. Mice treated with CRISPR/Cas9 successfully silenced gene expression for 9 days and 2 h before and 4 h after HSV‐2 vaginal challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Delivery of siRNA targeting UL 39 and DNA polymerase genes in HSV-1 has been proved to effectively and specifically knockdown the corresponding gene expression and inhibit HSV-1 replication in vitro. 18,19 In addition, CRISPR/Cas9based microbicides effectively protect mice from HSV-1 infection when administered intravenously 20 ; this finding will be discussed in detail later in this review. With respect to HPV, over 90% of human cervical cancers are a result of abnormal cell proliferation driven by HPV oncoproteins.…”
mentioning
confidence: 98%
“…There is evidence that HSV-1 may be involved in the development of such neuropathologies as Alzheimer’s disease [ 4 ], multiple sclerosis [ 5 ], meningitis and encephalitis [ 6 ]. As other sexually transmitted infections, HSV-1 genital herpes may contribute to the development of infertility, negatively affect pregnancy, up to fetal death, cause congenital and neonatal infections [ 7 , 8 ]. Reactivation of herpesviruses has also been observed in patients infected with SARS-CoV-2 [ 9 , 10 ], the causative agent of the ongoing COVID19 pandemic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HSV infections have become a major public health concern. According to a WHO investigation, more than one billion people worldwide are infected with HSV-1-caused oral herpes, and an estimated 500 million are infected with HSV-2caused genital herpes (Kushch et al, 2021). Acyclovir (ACV) is widely used to treat HSV infections and inhibits HSV-specific DNA polymerase and impedes HSV replication and further infection (Brigden and Whiteman, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…HSV infections have become a major public health concern. According to a WHO investigation, more than one billion people worldwide are infected with HSV-1-caused oral herpes, and an estimated 500 million are infected with HSV-2-caused genital herpes ( Kushch et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%